RECEPTION ANALYSIS OF HORROR GAME CONTENT ON THE WINDAH BASUDARA YOUTUBE CHANNEL - Intan Dwi Suryani; Andika Sanjaya (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
This study aims to analyze audience acceptance of horror games on Windah Basudara's YouTube channel with a qualitative approach and using Stuart Hall's recipe theory. Using interview techniques, this study explores many aspects of interpretation, the influence of creator delivery behavior, and sociopsychological aspects that influence interpretation. The results of the study show that audiences interpret the content in a variety of ways - there are dominant responses to resistance, mostly influenced by their personal experiences, culture, and the social context that surrounds them. Windah Basudara's expressive and interactive content delivery style also has an impact on the viewing experience and interpretation that varies for each individual. This study makes an important contribution in examining the interaction of digital media with emotional, interactive and contemporary content, on the one hand, and responds to the dynamics of rapid comparison of influences on content creation on audiences in the digital era.